PENGARUH PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SUBTEMA BERSYUKUR ATAS KEBERAGAMAN - Rais Hidayat; Resyi Abdul Gani; Yuyun Elizabeth Patras; Dewi Sulastri (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
The purpose of this research is to explain the effect of the implementation of the discovery learning model on learning outcomes for the Sub-theme of Gratitude for Diversity. This study used an experimental method with a quasi-experimental type of two-group design at the Cibarusah Jaya 04 State Elementary School, West Java. Data collection techniques using test instruments, data analysis using descriptive statistics, testing prerequisite analysis and finally hypothesis testing using t test. The population is 72 students with the sampling technique using purposive sampling, so that 72 students are sampled. This research was conducted in the first semester of the 2021/2022 academic year. The results of the research show that there is an effect of the implementation of the Discovery Learning model on learning outcomes for the Sub-theme of Gratitude for Diversity. This can be seen from the N-Gain in the experimental class group of 80, while the control class group got an N-Gain value of 71. The completeness of learning outcomes obtained by the experimental group was 92% while in the control class group it was 56%. The results of testing the research hypothesis show that H0 is rejected and Ha is accepted because tstatistic (2.9785) > ttable (1.99). Based on these findings, the use of the discovery learning model is highly recommended to improve the learning outcomes in elementary schools